Hydrodeoxygenation of Xylose Isopropylidene Ketal Over Pd/HBEA Catalyst for the Production of Green Fuels - Souza, Matheus O.; Pereira, Sergio C.; Lau, Lam Y.; Soter, Leandro; Pereira, Marcelo M. (Frontiers in Chemistry, 2021)
1,2:3,5-Di-O-Isopropylidene--D-xylofuranose (DX) is a major component of a new bio-crude: a viscous oil presenting petroleum-friendly properties produced by ketalization of sugarcane bagasse. This paper reported the study of DX HDO (hydro-deoxygenation) over Pd/HBEA catalyst in a batch reactor at 250°C. Effects of hydrogen pressure from 10 to 40 bars, catalyst/DX ratio from ½ to 2 and reaction time 0 to 24h were investigated. A range of conditions for complete hydrodeoxygenate DX into alkanes with Pd/HBEA catalyst was found. In these conditions, low coke yield with water as the principal deoxygenated product were obtained. Further, higher amounts of alkanes containing seven or more carbons (A7+) were favored at 30 bar of hydrogen pressure, Cat/DX ratio=2 and short reaction time. Products analysis that accompanied the above variations during reaction time led to general insights on reaction pathways. First, in the presence of DX, effective n-hexane conversion was not observed on experiments of low Catalyst/DX ratio (½), or in the initial period of high Cat/DX ratio, suggesting DX is much more successful than n-hexane to compete for active sites. Then it was observed the formation of a pool of oxygenate compounds such as furans, ketones, and carboxylic acids along with lighter and heavier alkanes. Hence, the aforementioned oxygenates may undergo reactions such as aldol condensation with subsequent hydrodeoxygenation reaction, generating heavier alkanes.